Systematic Management of Business English Modules for Speaking Competence Enhancement: A Descriptive Study of Youth Entrepreneurship Development - Iriani, Timur; Rosa, Ade Tutty R (Papanda Publisher, 2025)
The VUCA world and high unemployment rates present significant challenges to Indonesian youth, particularly regarding English proficiency deficits that limit global competitiveness. This study examines the management of a Business English Module designed to improve speaking competence through presentation techniques among youth organization members. A qualitative descriptive study was conducted at Karang Taruna Cijagra Village involving 55 active members aged 16-20 years with diverse educational backgrounds. Data collection employed observations, semi-structured interviews, and documentation analysis. The program implementation followed George R. Terry's management framework (Planning, Organizing, Actuating, Controlling) integrated with English for Specific Purposes (ESP) and Competence-Based Education (CBE) approaches. Data analysis utilized systematic reduction, presentation, and verification procedures. The systematic management approach yielded significant improvements in speaking competence across all participants. Pre-test results indicated 76.4% possessed basic English knowledge, while only 23.6% had business English exposure. Post-implementation assessments revealed 85% of participants achieved significant improvement in fluency, clarity, intonation, and confidence. The Personal Canvas technique demonstrated 91-100% completion rates across progressive stages. Active speaking time increased from 3 to 12 minutes per session, while business plan presentations achieved 89% success rates with average quality scores of 7.2/10. The integration of management principles with ESP and CBE approaches created an effective framework for Business English instruction. The documented improvements validate the effectiveness of presentation-based learning in developing both language skills and entrepreneurial mindset, supporting the dual objectives of reducing unemployment while enhancing global competitiveness among Indonesian youth.